Emergence and spread of a new community-genotype methicillin-resistant Staphylococcus aureus clone in Colombia (2017)
Background Community-genotype methicillin-resistant Staphylococcus aureus (CG-MRSA) clones are a global concern due to their resistance and increased virulence and their ability to cause infections both hospitalized patients and healthy people in the community. Here, we characterize 32 isolates of a new CG-MRSA clone. These isolates were identified in four cities in Colombia, South America. Methods The isolates were recovered from four different epidemiological and prospective studies that were conducted in several regions of Colombia. Molecular characterizations included multilocus sequence typing; pulsed-field gel electrophoresis; SCCmec, agr and spa typing; and whole-genome sequencing. Results All isolates belonged to ST923 (clonal complex 8), harbouring SCCmec IVa and a spa type t1635 and lacking an arginine catabolism mobile element. The isolates were classified as COL923, were resistant to at least one non-beta-lactam antibiotic, and exhibited high frequencies (>60%) of resistance to macrolides and tetracycline. Using whole-genome sequencing, we found that this new clone harbours novel prophage 3 and beta-island structures and a slightly different pathogenicity island 5. Moreover, isolates belonging to the COL923 clone are grouped in a different clade than USA300 and USA300-LV. Conclusion Our results show the emergence and spread of the COL923 clone in different cities in Colombia. This clone is resistant to several antibiotics and possesses new structures in its mobile genetic elements.